Grindr, Scruff, and on the Hunt: Predictors of Condomless Anal Sex, Internet Use, and Mobile Application Use Among Men Who Have Sex With Men. (May 2017) - Whitfield, Darren L.; Kattari, Shanna K.; Walls, N. Eugene; Al-Tayyib, Alia
In 2016, gay, bisexual, and other men who have sex with men (MSM) comprise more than half of all new HIV diagnoses in the United States, with the primary mode of infection being condomless anal sex (CAS). While studies report an association between use of Internet-based social networking sites and increased CAS, the research on the relationship between cell phone mobile applications (e.g., Grindr, Scruff, Jack'd) and CAS is much less developed. The present study examines whether the manner in which gay, bisexual, and other MSM find sexual partners predicts an increase in likelihood of engaging in CAS in an urban, noncoastal U.S. city. Conducting a secondary data analysis of the 2011 National HIV Behavioral Surveillance survey for Denver ( N = 546), the authors performed binary logistic regression analyses to assess the models that predict how MSM find sexual partners, and the odds of engaging in CAS. While the results suggest that age and race are associated with the mode of finding sexual partners, using the Internet or a mobile app to find sexual partners was not predictive of CAS ( Z Wald = .41, p = .52; Z Wald = .80, p = .37). In terms of HIV prevention, these findings suggest a need for intervention to address HIV prevention on multiple levels (e.g., individual, group, community).